صور الإطناب في الوصية الوقفية لعلي رضي الله عنه: دراسة بلاغية - القحيز، ريم بنت زيد بن عبدالرحمن (جامعة تعز فرع التربة - دائرة الدراسات العليا والبحث العلمي, 2023)
تناولت الدراسة أسلوب الإطناب وأثره في إيصال المعنى، من خلال تحليل صور الإطناب في الوصية الوقفية لعلي رضي الله عنه، حيث تمثل الوصية لونا من ألوان الكتابة المعتبرة عند المسلمين، وكان من أبرز نتائج الدراسة: - بسط الكلام صورة من صور الإطناب تعكس حرص الواقف على تأكيد ما يريد بيانه من الموضوعات والمعاني. - الإيضاح بعد الإبهام في الوصية لزيادة التوثيق لملكية الأعيان للواقف، ومنعا للبس في القصد. - جاء أسلوب الإطناب متوافقا مع الحالة النفسية التي يشعر بها الموصي وهو يستحضر انقطاعه عن ملكه، وحاجته لثواب العمل. - من أغراض الاحتراس في الوصية الوقفية إفهام الناظر على الوقف؛ تجنبا لاختلاف الفهم، وحرصا على تنفيذ الوصية كما يريدها الواقف. وأخيرا أوصي الباحثين بتنويع النصوص المقصودة بالتحليل البلاغي لاستكشاف معان بلاغية جديدة تتنوع بتنوع النصوص البليغة وتتعدد بتعدد أغراضها. The study dealt with the style of verbosity and its impact on conveying the meaning, by analyzing the images of verbosity in the endowment will of Ali, may God be pleased with him, as the will represents one of the colors of writing considered by Muslims. Among the most prominent search results were: - Expanding speech is a form of redundancy that reflects the keenness of the person standing to confirm what he wants to state of topics and meanings. - Clarification after ambiguity in the will to increase documentation of the ownership of the objects of the endower, and to prevent confusion in the intent. - The verbosity style was consistent with the psychological state felt by the testator as he recalled his severance from his possession, and his need for the reward of work. - One of the purposes of caution in the waqf will is to inform the beholder of the waqf; In order to avoid a difference in understanding, and in order to implement the will as the endower wants it. Finally, I recommend researchers to diversify the texts intended for rhetorical analysis to explore new rhetorical meanings that vary with the diversity of rhetorical texts and multiply with the multiplicity of their purposes.
Keywords: أسلوب الإطناب -- الأساليب البلاغية -- الدراسات البلاغية -- علي، بن ابي طالب، خليفة المسلمين، ت. 40 هـ